Improving the recombinant human erythropoietin glycosylation using microsome supplementation in CHO cell‐free system. Issue 5 (13th February 2018) - Gurramkonda, Chandrasekhar; Rao, Aniruddha; Borhani, Shayan; Pilli, Manohar; Deldari, Sevda; Ge, Xudong; Pezeshk, Niloufar; Han, Tzu‐Chiang; Tolosa, Michael; Kostov, Yordan; Tolosa, Leah; Wood, David W.; et al.
Abstract: Cell‐Free Protein Synthesis (CFPS) offers many advantages for the production of recombinant therapeutic proteins using the CHO cell‐free system. However, many complex proteins are still difficult to express using this method. To investigate the current bottlenecks in cell‐free glycoprotein production, we chose erythropoietin (40% glycosylated), an essential endogenous hormone which stimulates the development of red blood cells. Here, we report the production of recombinant erythropoietin (EPO) using CHO cell‐free system. Using this method, EPO was expressed and purified with a twofold increase in yield when the cell‐free reaction was supplemented with CHO microsomes. The protein was purified to near homogeneity using an ion‐metal affinity column. We were able to analyze the expressed and purified products (glycosylated cell‐free EPO runs at 25–28 kDa, and unglycosylated protein runs at 20 kDa on an SDS–PAGE), identifying the presence of glycan moieties by PNGase shift assay. The purified protein was predicted to have ∼2, 300 IU in vitro activity. Additionally, we tested the presence and absence of sugars on the cell‐free EPO using a lectin‐based assay system. The results obtained in this study indicate that microsomes augmented in vitro production of the glycoprotein is useful for the rapid production of single doses of a therapeutic glycoprotein drug and to rapidly screen glycoprotein constructs in the development of these types of drugs. CFPS is useful for implementing a lectin‐based method for rapid screening and detection of glycan moieties, which is a critical quality attribute in the industrial production of therapeutic glycoproteins. Abstract : In this work, we report the production of recombinant erythropoietin (EPO) using CHO cell‐free system. Using this method, EPO was expressed and purified with a two‐fold increase in yield when the cell‐free reaction was supplemented with CHO microsomes. The purified protein was predicted to have ∼2, 300 IU in vitro activity. Additionally, we tested the presence and absence of sugars on the cell‐free EPO using a lectin‐based assay system. The results obtained in this study indicate that microsomes augmented in vitro production of the glycoprotein is useful for the rapid production of single doses of a therapeutic glycoprotein drug and to rapidly screen glycoprotein constructs in the development of these types of drugs. CFPS is useful for implementing a lectin‐based method for rapid screening and detection of glycan moieties, which is a critical quality attribute in the industrial production of therapeutic glycoproteins.